Spousal Trust Alignment and Intra-Household Cooperation - Henrike Sternberg; Janina Isabel Steinert; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2024)
We implement a binary trust game between 211 married couples from low-income households in urban India. In a separate experiment, these spouses randomly received either only a joint savings device (control) or, additionally, a device for individual usage (treatment). Combining data from both experiments, we examine how the impact of the strategically usable savings device varies by spouses' trust and trustworthiness, particularly, by their alignment. We find that wives also receiving the individual device reported significantly higher savings only when spouses' decisions in the trust game were aligned. When decisions were misaligned, the coefficient turned negative. The results suggest that, under positive alignment (wives justifiably trusting their husbands), higher savings were achieved through wives' increased involvement in household decisions. Conversely, in couples where wives (justifiably) mistrust their husbands, they used the private device to hide money to realize higher savings. Our findings encourage household-based interventions to consider spouses' (mis)perceptions about intra-household cooperation.
Keywords: D1; D8; D91; J12; O12; 330; Spousal Trust; Household Decision Making; Semi-Cooperative Household Model; Trust Game; Saving Interventions; Concealment Behavior